Integral Valued Numerical Data: Measure of Central Tendency - Dhritikesh Chakrabarty (Partners Universal International Research Journal, 2022)
In the situation where the data set to be studied consists of integral valued numerical observations, the existing measures of central tendency may fail to provide the value, which is a valid one, of central tendency since the values provided by them are not bound to be integers. A valid measure of the same, in the case of such data, has been derived in this study. This article describes the derivation of the measure and its application in the data on number of rainy days at New Delhi.